In search of Gandhi: Essays and reflections - B R Nanda; NANDA (B R) (New Delhi Oxford University Press, 2002)
This volume presents twenty-nine essays that encompass the author$1 (Bs reflections on various facets of Mahatma Gandhi$1 (Bs life and thought. These essays were products of research which started on that fateful winter evening of 30 January 1948 and were written on different occasions, and with varied themes, length, and depth. They were designed to respond to the interest of the particular audience for which they were written. The essays explore Gandhi$1 (Bs fight for Indian freedom in South Africa and evaluate the influence of the South African movement in his political career in India. They also mention several attempts made in his life, and describe his relationship with various issues and personalities including racialism, Pan-Islamism, Swami Vivekananda, and Charles Andrews. The reception of Gandhi$1 (Bs ideas, his accomplishments, and his legacies are also examined in these essays.s
Keywords: Indian History; Essyas and Reflections; Gandhi and Nehru